Crystallization scale preparation of a stable GPCR signaling complex between constitutively active rhodopsin and G-protein. - Shoji Maeda; Dawei Sun; Ankita Singhal; Marcello Foggetta; Georg Schmid; Joerg Standfuss; Michael Hennig; Roger J P Dawson; Dmitry B Veprintsev; Gebhard F X Schertler (PLoS ONE, 2014)
The activation of the G-protein transducin (Gt) by rhodopsin (Rho) has been intensively studied for several decades. It is the best understood example of GPCR activation mechanism and serves as a template for other GPCRs. The structure of the Rho/G protein complex, which is transiently formed during the signaling reaction, is of particular interest. It can help understanding the molecular details of how retinal isomerization leads to the G protein activation, as well as shed some light on how GPCR recognizes its cognate G protein. The native Rho/Gt complex isolated from bovine retina suffers from low stability and loss of the retinal ligand. Recently, we reported that constitutively active mutant of rhodopsin E113Q forms a Rho/Gt complex that is stable in detergent solution. Here, we introduce methods for a large scale preparation of the complex formed by the thermo-stabilized and constitutively active rhodopsin mutant N2C/M257Y/D282C(RhoM257Y) and the native Gt purified from bovine retinas. We demonstrate that the light-activated rhodopsin in this complex contains a covalently bound unprotonated retinal and therefore corresponds to the active metarhodopin II state; that the isolated complex is active and dissociates upon addition of GTPγS; and that the stoichiometry corresponds to a 1∶1 molar ratio of rhodopsin to the heterotrimeric G-protein. And finally, we show that the rhodopsin also forms stable complex with Gi. This complex has significantly higher thermostability than RhoM257Y/Gt complex and is resistant to a variety of detergents. Overall, our data suggest that the RhoM257Y/Gi complex is an ideal target for future structural and mechanistic studies of signaling in the visual system.